Conjunctivitis in dupilumab clinical trials. (7th May 2019) - Akinlade, B.; Guttman‐Yassky, E.; de Bruin‐Weller, M.; Simpson, E.L.; Blauvelt, A.; Cork, M.J.; Prens, E.; Asbell, P.; Akpek, E.; Corren, J.; Bachert, C.; Hirano, I.; et al.
Summary: Background: Dupilumab blocks the shared receptor component for interleukin (IL)‐4 and IL‐13. It is approved in the U.S.A. for patients aged ≥ 12 years with moderate‐to‐severe atopic dermatitis (AD) uncontrolled by topical prescription medicines or who cannot use topical medicines, for patients in Japan whose AD is uncontrolled with existing therapies, for patients with moderate‐to‐severe AD in Europe who are candidates for systemic therapy and for patients aged ≥ 12 years for maintenance treatment of moderate‐to‐severe asthma uncontrolled with their current medicines. AD trials have reported increased incidence of conjunctivitis for dupilumab vs. placebo. Objectives: To characterize further the occurrence and risk factors of conjunctivitis in dupilumab clinical trials. Methods: We evaluated randomized placebo‐controlled trials of dupilumab in AD ( n = 2629), asthma ( n = 2876), chronic rhinosinusitis with nasal polyps (CRSwNP) ( n = 60) and eosinophilic oesophagitis (EoE) ( n = 47). Results: In most AD trials, dupilumab‐treated patients had higher conjunctivitis incidence than placebo controls. Higher baseline AD severity and previous history of conjunctivitis were associated with increased conjunctivitis incidence. Conjunctivitis was mostly mild to moderate. Most cases recovered or resolved during the treatment period; two patients permanently discontinued dupilumab due to conjunctivitis or keratitis. Common treatments included ophthalmic corticosteroids, antibiotics, and antihistamines or mast cell stabilizers. Most cases were diagnosed by the investigators. In asthma and CRSwNP trials, the incidence of conjunctivitis was lower for both dupilumab and placebo than in AD trials; dupilumab did not increase the incidence compared with placebo. In the EoE trial, no patients had conjunctivitis. Conclusions: Conjunctivitis was more frequent with dupilumab treatment in most AD trials. In dupilumab trials in other type 2 diseases, incidence of conjunctivitis was overall very low, and was similar for dupilumab and placebo. In AD, the incidence of conjunctivitis was associated with AD severity and prior history of conjunctivitis. The aetiology and treatment of conjunctivitis in dupilumab‐treated patients require further study. What's already known about this topic? Ocular disorders, including allergic conjunctivitis, are common in patients with atopic dermatitis (AD). In most dupilumab AD trials, dupilumab‐treated patients had higher conjunctivitis incidence than those receiving placebo. Most cases were mild to moderate and recovered or were recovering during study treatment; study treatment discontinuation due to conjunctivitis was rare. Conjunctivitis incidence was very low and similar for dupilumab and placebo in clinical trials in asthma, chronic rhinosinusitis with nasal polyps and eosinophilic oesophagitis. What does this study add? This analysis confirms and extends the results of the individual clinical trials. Baseline disease‐related factors, including AD severity, prior conjunctivitis history and certain biomarkers (thymus and activation‐regulated chemokine, IgE, eosinophils), were associated with increased incidence of conjunctivitis. Patients who responded well to dupilumab had reduced incidence of conjunctivitis. Further study is needed to elucidate the aetiology and treatment of conjunctivitis in dupilumab‐treated patients with AD. Abstract : Linked Editorial : Chia‐Yu Chu. Br J Dermatol 2019; 181 :436–437 . Plain language summary available online Respond to this article